Allelopathic effect of Capsicum chinense, Dianthus caryophyllus, and Sorghum bicolor on seeds - Barroso-Ake, Alisa Clementina; Arredondo-Valdés, Roberto; Carnero-Avilés, Leslie; Ilina, Anna; Ramos-González, Rodolfo (Ecosistemas y Recursos Agropecuarios, 2025)
Weeds represent a threat to agricultural production, causing significant losses in various crops. Chemically synthesized herbicides have been widely used for their control; however, their use entails environmental and resistance problems that pose important challenges. Aware of this problem, we have sought to develop more sustainable alternatives within the framework of sustainable agriculture. Plant extracts offer promising characteristics, such as their degradability, low cost, and effectiveness. In this context, the main objective of this work is to develop an alternative based on plant extracts from Capsicum chinense L., Dianthus caryophyllus L., and Sorghum bicolor L. With HPLC/MS and GC-MS/MS analysis, we were able to find antioxidant compounds (DPPH), measure total phenols, and find volatile compounds. Additionally, we conducted germination inhibition tests on model seeds of Phaseolus vulgaris L. and Avena sativa L., utilizing the various extracts under evaluation. The results revealed the presence of various families of compounds, which contributed to the allelopathic activity of the extracts. The model seeds showed inhibition of germination, indicating a potential pre-emergence herbicidal effect of the selected treatments. The plant extracts analyzed exhibit a wide variety of bioactive and significant herbicidal activities. Therefore, we postulate its use as a viable and sustainable alternative for controlling weed germination in agricultural systems, potentially promoting more environmentally friendly agricultural practices.
Keywords: Natural extracts; Weed control; Bioactive compounds; Germination inhibition